Language Difficulties in School-Age Children With Developmental Dyslexia. (May 2022) - Price, Kaitlyn M.; Wigg, Karen G.; Misener, Virginia L.; Clarke, Antoine; Yeung, Natalie; Blokland, Kirsten; Wilkinson, Margaret; Kerr, Elizabeth N.; Guger, Sharon L.; Lovett, Maureen W.; Barr, Cathy L.
Developmental dyslexia (DD) is a common reading disability, affecting 5% to 11% of children in North America. Children classified as having DD often have a history of early language delay (ELD) or language impairments. Nevertheless, studies have reported conflicting results as to the association between DD-ELD and the extent of current language difficulties in children with DD. To examine these relationships, we queried the parents of school-age children with reading difficulties on their child's early and current language ability. Siblings were also examined. Children were directly assessed using quantitative tests of language and reading skills. To compare this study with the literature, we divided the sample ( N = 674) into three groups: DD, intermediate readers (IR), and skilled readers (SR). We found a significant association between DD and ELD, with parents of children in the DD/IR groups reporting their children put words together later than the SR group. We also found a significant association between DD and language difficulties, with children with low reading skills having low expressive/receptive language abilities. Finally, we identified early language predicted current language, which predicted reading skills. These data contribute to research indicating that children with DD experience language difficulties, suggesting early recognition may help identify reading problems.